Prevalence, Severity and Factors Associated with Dental Caries Among School Adolescents in Uganda: A Cross-Sectional Study - Ndagire,Barbara (2020)
Abstract Dental caries is one of the most prevalent diseases in developing countries. However, there is limited data on the prevalence and factors associated with dental caries in Ugandan adolescents. The purpose of the present study was to describe the prevalence, severity of dental caries and to determine the factors associated with the disease among school adolescents in Uganda. A cross sectional study was conducted at two secondary schools from Kampala (n=197) and Mukono (n=209) districts, Uganda. At both schools, random sampling was used to select the participating classes and the 406 adolescents (11-19 years) eligible to participate in the research. Dental caries was examined using the Decayed, Missing and Filled Teeth (DMFT) index, and a questionnaire was used to collect other relevant data in form of an oral interview. The data were analyzed using STATA version 12. The data was declared as survey data and all analyses were done with svy command. The prevalence of caries was determined as a percentage of individuals with DMFT score ≥1. Modified Poisson regression models were utilized to assess the association between prevalence, severity of dental caries and independent variables. The overall prevalence of dental caries was 66.0% and mean DMFT score of 2.18±2.67. Dental caries prevalence and severity were significantly (p<0.05) associated with tooth cleaning device, age and history of previous dental visit. There was a high prevalence and severity of dental caries among adolescents, which emphasizes the urgent need to develop and design appropriate interventions to reduce the disease burden.